The perilous leap between exploration and exploitation - Swift, Tim (Strategic Management Journal, 2016)
Research summary : R&D‐based exploration and exploitation are necessary in order for firms to have sustainable competitive advantage. Yet, transitioning between these orthogonal types of R&D is considered profound organizational change. Building on recent research showing that compact, significant changes in R&D expenditure is an antecedent to the transition between explorative and exploitative R&D, I show that this leap between exploration and exploitation is quite hazardous. The magnitude of changes in R&D expenditure, whether increases or decreases, is positively associated with organizational failure. Firms maintaining higher levels of absorptive capacity are more capable of surviving the leap from R&D‐based exploitation to exploration, and firms that do not use reductions in R&D expenditure to manipulate short‐term earnings performance are more likely to survive the leap from exploration to exploitation . Managerial summary : In order to survive and thrive, innovative companies must be able to exploit their existing competencies, and to explore for new ones once those current competencies decline in value. However, transiting from one form of innovation to the other is difficult because the skills required to explore are fundamentally opposed to those required to exploit. In this article, I describe how difficult this leap between exploration and exploitation can be. I show that the move between R&D‐based exploration and exploitation is related to organizational failure. In addition, firms that are superior learners are more likely to survive the leap from exploitation to exploration, and firms that are not cutting R&D expenditure to manipulate earnings are more likely to survive the leap from exploration to exploitation . Copyright © 2015 John Wiley & Sons, Ltd.